Nitric oxide combined with abscisic acid contributes to high-temperature tolerance in macroalga Gracilariopsis lemaneiformis - Luke Chu; Xiao Ying; Mingyue Li; Shixia Liu; Nianjun Xu; Xue Sun (Frontiers in Marine Science, 2025)
Introduction The economic macroalga Gracilariopsis lemaneiformis is widely cultivated in China, yet high temperatures in the summertime constrain its cultivation period on China’s southern coasts. Thus, it is of great significance to improve its heat tolerance. Nitric oxide (NO), a small signaling molecule, plays a vital role in resistance to abiotic stresses such as drought, salinity, and low/high temperature in higher plants. However, the role and underlying mechanism of NO in algae are still unclear. Methods Here, physiological assay and tandem mass tag (TMT)-labeled quantitative proteomics technique were used to elucidate the role of NO in resisting high-temperature-stressed G. lemaneiformis . And NO donor sodium nitroprusside (SNP), abscisic acid (ABA), NO scavenger, and ABA inhibitor were applied to explore the crosstalk of NO and phytohormone ABA. Results Physiological data showed that SNP promoted the algal growth (1.23-fold) and actual photosynthetic efficiency, yet reduced heat dissipation in G. lemaneiformis at 30℃. Proteomics results revealed that several KEGG pathways, including nitrogen metabolism, vitamin B6 metabolism, and glutathione metabolism, were significantly enriched after SNP treatment; meanwhile, a batch of differentially expressed proteins involved in carbohydrate metabolism and photosynthesis were also screened. In addition, SNP and/or ABA reduced malondialdehyde levels and promoted proline accumulation. Combined with the changes of endogenous NO and ABA levels, as well as their metabolic enzyme activities, it could be inferred that NO might act downstream of ABA. Discussion/Conclusion These findings demonstrate that NO and ABA can synergistically act against high-temperature stress in G. lemaneiformis . The present study will provide a valuable insight into understanding the mechanism of NO regulating high-temperature tolerance in macroalgae.